2021
DOI: 10.1002/psp4.12727
|View full text |Cite
|
Sign up to set email alerts
|

Erdafitinib’s effect on serum phosphate justifies its pharmacodynamically guided dosing in patients with cancer

Abstract: A population pharmacokinetic (PK)-pharmacodynamic (PD) model was developed using data from 345 patients with cancer. The population PK-PD model evaluated the effect of erdafitinib total and free plasma concentrations on serum phosphate concentrations after once-daily oral continuous (0.5-12 mg) and intermittent (10-12 mg for 7 days on/7 days off) dosing, and investigated the potential covariates affecting erdafitinib-related changes in serum phosphate levels.Phosphate is used as a biomarker for erdafitinib's e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Thus, this suggested that the application of the nanodrug effectively reduced the off-target side effects of erdafitinib. Patients may develop hyperphosphatemia after the administration of erdafitinib, which would lead to dose reduction or intermittent or permanent treatment interruption . Therefore, this work developed a new strategy to mitigate the side effects of erdafitinib, which might open up the possibility for its broader clinical application.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this suggested that the application of the nanodrug effectively reduced the off-target side effects of erdafitinib. Patients may develop hyperphosphatemia after the administration of erdafitinib, which would lead to dose reduction or intermittent or permanent treatment interruption . Therefore, this work developed a new strategy to mitigate the side effects of erdafitinib, which might open up the possibility for its broader clinical application.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] Despite the promising results, the number of works applied to real clinical scenario is still limited. 24 In this paper, a new framework combining RL and PK-PD modeling was proposed to improve precision dosing of erdafitinib (Balversa, Janssen Pharmaceutical companies), an anticancer compound approved by the US Food and Drug Administration (FDA) for the treatment of metastatic urothelial carcinoma [31][32][33][34] Erdafitinib is characterized by a narrow therapeutic window and high IIV of the response. 32 The serum phosphate concentration, 35 [PO 4 ] serum , is the most important efficacy and toxicity biomarker.…”
Section: Reinforcement Learning and Pk-pd Models Integration To Perso...mentioning
confidence: 99%
“…24 In this paper, a new framework combining RL and PK-PD modeling was proposed to improve precision dosing of erdafitinib (Balversa, Janssen Pharmaceutical companies), an anticancer compound approved by the US Food and Drug Administration (FDA) for the treatment of metastatic urothelial carcinoma [31][32][33][34] Erdafitinib is characterized by a narrow therapeutic window and high IIV of the response. 32 The serum phosphate concentration, 35 [PO 4 ] serum , is the most important efficacy and toxicity biomarker. 31,32,36 In particular, [PO 4 ] serum ≥ 5.5 mg/dL correlated with a better response to treatment, 31 whereas [PO 4 ] serum < 7 mg/dL represents the safety threshold for hyperphosphatemia, the major cause of drug-related adverse events.…”
Section: Reinforcement Learning and Pk-pd Models Integration To Perso...mentioning
confidence: 99%
See 1 more Smart Citation
“…When bedaquiline is reintroduced after dose interruption, concerns exist about the risk of QT‐prolongation and potential ventricular arrhythmias, and the results presented by the authors demonstrate a potential strategy for safe reintroduction of the drug. Along similar lines, Marco‐Ariño et al 9 use a PopPD model to address pupillary reflex dilation caused by remifentanil, an opioid used as an analgesic during surgery, and Dosne et al 10 use PK/PD modeling for individualized dosing of erdafitinib, a drug that can treat urothelial carcinoma but can cause acute hyperphosphatemia in some patients. Together, these articles demonstrate the centrality of pharmacometrics approaches in ensuring that highly useful drugs do not cause adverse events due to improper dosing.…”
mentioning
confidence: 99%